Genetic variability of Candida albicans in HIV/AIDS patient with and without ARV therapy and non HIV/AIDS - Retno Puji Rahayu; Widiyanti P; Arfijanto M (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Oral candidiasis is the mostly found oral manifestation in HIV/AIDS infected patient caused by immunocompromised especially immunodeficiency. Clinical symptoms is severe pain in oral cavity and dry mouth because of xerostomia which cause the loss of appetite. Candida albicans (C. albicans) is normal flora in oral cavity which plays as opportunistic pathogen and also the cause of oral candidiasis. Almost 90% of HIV–infected patient have oral candidiasis. This condition is clinical problem which has not been well-managed yet. C. albicans colonized oral mucous cavity has different genetic variability for each strain. Phenotype of C. albicans has been determined by genetic factor and environtment. This condition stimulate differences of genotype among various strain of C. albicans in the world. Purpose: The purpose of this research is to analyze the genetic variability of C.albicans which colonized in the mucous oral cavity of HIV/AIDS patient in Surabaya in the treatment with and without ARV therapy and non HIV/AIDS. Methods: This research has been identify and characterize the prevalent strain of C. albicans isolat in Surabaya (East Java) in HIV/AIDS infected patient with oral candidiasis by method of Iatron candidal check. The highlight of this research including cytology examination by Papanicoloau staining, C. albicans culture, spheroplast making, DNA isolation and genetic variability checking by randomly amplyfied polymorphism DNA (RAPD). Results: C. albicans colonizing oral mucosa of non-HIV patients had a predisposition of farther genetic relationship (genetic distance of 0.452) with C. albicans colonizing oral mucosa of HIV ARV and HIV non-ARV patients. The genetic distance was ranging between 0 and 1, where 9 was long genetic distance and 1 was short genetic distance. In contrast, C. albicans colonizing oral mucosa of HIV ARV have predisposition of closer genetic relationship (genetic distance of 0.762) with C. albicans colonizing oral mucosa of HIV non-ARV patients. Conclusion: The conclusion of this research were C.albicans colonizing HIV/AIDS patiens with and without ARV showed no high genetic variability between C.albicans isolate in HIV patients. There fore, the character of C.albicans colonizing HIV ARV and HIV non-ARV patients had similar genotype predisposition of closer relationship value with C.albicans colonizing oral mucosa non HIV patients.Latar belakang: Oral candidiasis merupakan manifestasi kelainan rongga mulut yang paling sering timbul pada penderita HIV/AIDS karena kondisi immunocompromised terutama defisiensi imun. Gejala klinisnya berupa nyeri hebat di rongga mulut dan mulut kering karena xerostomia yang menyebabkan hilangnya nafsu makan. Candida albicans (C. albicans) berperan sebagai patogen oprtunistik dan merupakan penyebab Kandidiasis rongga mulut. Hampir 90% penderita terinfeksi HIV mengalami kandidiasis rongga mulut. Kondisi ini merupakan masalah klinis yang belum teratasi dengan baik. Kolonisasi C. albicans di mukosa rongga mulut mempunyai variabilitas genetic yang berbeda untuk tiap strainnya. Fenotip C. albicans ditentukan oleh faktor genetic dan lingkungan. Kondisi ini menstimulir perbedaan genotip di antara berbagai strain C. albicans di dunia. Tujuan: Tujuan penelitian ini adalah meneliti korelasi antara hubungan genetik yang menunjukkan variasi genetik kolonisasi C. albicans pada rongga mulut dan insidens kandidiasis rongga mulut pada penderita HIV/AIDS dan non-HIV/AIDS. Metode: Penelitian ini mengidentifikasi dan mengkarakterisasi strain Candida albicans isolat Surabaya (Jawa Timur) pada penderita HIV/AIDS dengan kandidiasis rongga mulut dengan metode iatron candidal check. Penekanan dalam penelitian ini termasuk pada pemeriksaan sitologi dengan pengecatan Papanicoloau, kultur C. albicans, pembuatan spheroplast, isolasi DNA dan pemeriksaan variabilitas genetik dengan randomly amplified polymorphism DNA (RAPD). Hasil: C. albicans yang berkolonisasi di rongga mulut pada penderita non-HIV mempunyai predisposisi hubungan genetik (jarak genetik 0.452) dengan C. albicans yang berkolonisasi di rongga mulut pada penderita HIV yang mendapatkan terapi ARV dan non ARV. Jarak genetic bervariasi antara 0 dan 1, dimana 9 dalah jarak genetik terpanjang and 1 adalah jarak genetik terpendek. Sebaliknya, C. albicans yang berkolonisasi di rongga mulut pada penderita HIV yang menerima terapi ARV memiliki predisposisi hubungan genetic yang lebih dekat (jarak genetic 0.762) dibandingkan C. albicans yang berkolonisasi di rongga mulut pada penderita HIV non-ARV. Kesimpulan: Sebagai kesimpulan, penelitian ini menunjukkan bahwa C. albicans isolate Surabaya yang mengkolonisasi penderita HIV/AIDS dengan ARV dan non ARV memiliki hubungan kekerabatan genetik yang sama dibanding dengan pasien non HIV/AIDS.